Effect of dentifrices on their remineralizing potential in artificial carious lesions: An in situ study - Satyawan Gangaramji Damle; Aditi Bector; Dhanashree Damle; Simranjeet Kaur (Wolters Kluwer Medknow Publications, 2016)
Background: The eventual sequel of dental caries is determined by the dynamic equilibrium between pathological factors which lead to demineralization and protective elements, which in turn leads to remineralization. Remineralization is the natural process for noncavitated demineralized lesions and relies on calcium and phosphate ions assisted by fluoride to rebuild a new surface on existing crystal remnants in subsurface lesions remaining after demineralization. Hence, the present study was designed to evaluate the efficacy of fluoride dentifrices in remineralizing artificial caries-like lesions in situ. Materials and Methods: A double-blind, randomized study with an initial washout period of 7 days was carried out for 3 weeks. Twenty volunteers were enrolled, who wore the intraoral cariogenicity test appliance having enamel slabs incorporated into them, for 3 weeks. 10 participants were instructed to use Group A dentifrice (fluoride) and the other 10 Group B dentifrice (nonfluoride) for brushing their teeth. The enamel slabs were analyzed by surface microhardness testing and scanning electron microscopy (SEM) at 3 intervals. Results: No significant differences was seen in the microhardness values recorded for Group A and Group B at baseline and after demineralization (P > 0.05); however Group B exhibited lesser microhardness compared to Group A, after intra-oral exposure (P < 0.05). In the SEM analysis, the Group A enamel surfaces had more regular and longer crystallites to those of the Group B. Conclusion: Fluoride dentifrices avert the decrease in enamel hardness and loss of minerals from the enamel surface to a large extent as compared to the nonfluoride dentifrices.